Metabolomics Analysis Of Blood And Urine To Identify Alcohol-Dependence Biomarkers - Mostafa, Hamza Mohamed Amin (2015)
Alcohol misuse is a ravaging public health and social problem. Alcoholdependence (AD) is a phase of alcohol misuse in which the drinker consumes excessive amount of alcohol and have a continuous urge to consume alcohol. The current methods of alcohol dependence diagnosis are questionnaires and some biomarkers. However, both methods lack specificity and sensitivity. Metabolomics is a novel scientific field which may provide a novel method for the diagnosis of alcohol-dependence by using a sensitive and specific technique such as nuclear magnetic resonance (NMR). Our aim was to identify the metabolic fingerprint (metabotype) that is able to discriminate between AD, non-AD alcohol drinkers and controls using metabolomics approach. The reproducibility of the outcomes was also investigated. Blood and urine samples were collected from 30 alcohol-dependent (mean age: 45.7), 54 social drinkers (mean age: 39.5) and 60 controls (mean age: 37.1). Plasma was separated by centrifugation, then both plasma and urine samples were mixed with phosphate buffer which was prepared by dissolving di-sodium hydrogen phosphate (Na2HP04), sodium dihydrogen phosphate (NaH2P04), sodium 3-(trimethylsilyl)-propionate-2,2,3,3-